2019
DOI: 10.1002/ange.201813797
|View full text |Cite
|
Sign up to set email alerts
|

Artificial K+Channels Formed by Pillararene‐Cyclodextrin Hybrid Molecules: Tuning Cation Selectivity and Generating Membrane Potential

Abstract: Ac lass of artificial K + channels formed by pillararene-cyclodextrin hybrid molecules have been designed and synthesized.T hese channels efficiently inserted into lipid bilayers and displayed high selectivity for K + over Na + in fluorescence and electrophysiological experiments.The cation transport selectivity of the artificial channels is tunable by varying the length of the linkers between pillararene and cyclodexrin. The shortest channel showed specific transmembrane transport preference for K + over all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 107 publications
0
13
0
Order By: Relevance
“…Moreover, the rigid pillar backbone of PAs and its assembly in tubular structures have inspired its implementation in the development of artificial transmembrane channels for ion, water, and protein transport . Generally, PAs are functionalized with other macrocycles, peptide chains or other moieties, via click reactions or cabodiimide cross-linking to study the overall effect on the performance of the synthetic ion channels. …”
Section: Design and Construction Strategies Of Pillar[n]arene-based N...mentioning
confidence: 80%
See 1 more Smart Citation
“…Moreover, the rigid pillar backbone of PAs and its assembly in tubular structures have inspired its implementation in the development of artificial transmembrane channels for ion, water, and protein transport . Generally, PAs are functionalized with other macrocycles, peptide chains or other moieties, via click reactions or cabodiimide cross-linking to study the overall effect on the performance of the synthetic ion channels. …”
Section: Design and Construction Strategies Of Pillar[n]arene-based N...mentioning
confidence: 80%
“…It was observed that the shortest the linker, the higher the efficiency of K + mobility and K + selectivity, due to restricted flexibility (Figure d). In addition, the amphiphilic nature of this system (hydrophobic pillar[5]­arene and hydrophilic α-CD) allowed its incorporation into the lipid bilayer displaying high stability …”
Section: Applications Of Pillar[n]arene-functionalized Nanomaterialss...mentioning
confidence: 99%
“…As shown in Figure d, after adding 16mer (5 μM) to the extravesicular solution of LUVs, the fluorescence intensity of the extravesicular Safranin O dye (200 nM) increased obviously, indicating that a negative potential was generated from the outside to the inside of the membranes. It can be seen that the fluorescent emission reached a maximum plateau at 100–120 s and then gradually decreased along with depolarization process, which is a common phenomenon in highly selective ion channels . The Safranin O assay has convincingly confirmed the monodirectional movement of protons through the helix-based channel.…”
mentioning
confidence: 82%
“…It can be seen that the fluorescent emission reached a maximum plateau at 100−120 s and then gradually decreased along with depolarization process, which is a common phenomenon in highly selective ion channels. 43 The Safranin O assay has convincingly confirmed the monodirectional movement of protons through the helix-based channel. Furthermore, the membrane integrity and stability of the EYPC-based LUVs were further assessed by the 5(6)-CF leakage experiments.…”
mentioning
confidence: 94%
“…Unlike natural ion channels, artificial ionophores show low selectivity and lack stimuli-responsive behavior. Therefore, developing artificial ionophores with preference for a particular ion is an attractive area of research [39][40][41][42] .…”
mentioning
confidence: 99%